Photo-identification of humpback whales (Megaptera novaeangliae) between Iceland, Norway and Guadeloupe - Charles Patrick Lavin 1992- (2017)
The migration of the humpback whale (Megaptera novaeangliae) is one of the longest known of any mammal on earth. They migrate seasonally between several low-latitude breeding grounds and several high-latitude feeding grounds. The geographical segregation of feeding grounds through maternally-directed site philopatry and the spatial distribution of prey has helped identify five separate feeding grounds in the North Atlantic: Gulf of Maine, Eastern Canada (Newfoundland / Labrador, Gulf of St. Lawrence), West Greenland, Iceland and Norway. Breeding grounds in the North Atlantic have also been identified, with several located within the West Indies and a single one around the Cape Verde Islands. On the feeding grounds 738 individuals have been identified in Icelandic waters, 752 in northern Norwegian waters, and 320 in the Guadeloupe breeding ground of the eastern West Indies. Through photo-identification methods between Icelandic and Norwegian catalogues, four (n=4) humpback whales have been sighted in both feeding grounds, while matches with Guadeloupe display a higher contribution of Norwegian (2.51%) than Icelandic whales (0.94%). The matches between Iceland and Norway may show eastern-North Atlantic feeding humpbacks on a migratory “stop-over” between these high-latitude feeding grounds and lower latitude breeding grounds. The higher percentage of Norwegian whales to Icelandic whales matching with the Guadeloupe catalogue suggests that further eastern-feeding humpbacks are more present within the eastern extent of the West Indies breeding ground, possibly through migratory preference. För hnúfubaksins (Megaptera novaeangliae) er hin lengsta sem þekkist hjá nokkru spendýri jarðar. Hvalirnir færa sig eftir árstíðum á milli nokkurra æxlunarstöðva á lágum breiddargráðum og nokkurra fæðustöðva á hærri breiddargráðum. Landfræðileg aðgreining fæðustöðva í gegnum átthagatryggð, sem lærist í móðurlegg, svo og svæðisdreifing veiðidýra hefur leitt í ljós fimm afmörkuð fæðusvæði í ...